Психодидактичні проблеми інноваційної діяльності педагога у контексті застосування сучасних креативних технологій навчання - Осадченко, Інна; Ковальчук, Мар’яна (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті на основі аналізу наукових джерел та емпіричного матеріалу виокремлено та схарактеризовано психодидактичні проблеми та шляхи їх усунення щодо інноваційної діяльності педагога у контексті застосування сучасних креативних технологій навчання. Доведено, що вирішення вказаних проблем залежить від усвідомлення педагогом необхідності дидактичної підготовки та психологічної готовності до такого виду діяльності. The article deals with the analysis of scientific sources and empirical material. It defines and characterizes psycho-didactic problems and ways of their solution in the innovative activities of the teacher in the context of using modern creative educational technologies. We proved in the article that solution to psycho-didactic problems of innovative activities of the teacher in the context of using modern technologies of education depends on the teacher’s awareness as to the necessity of didactic training (technological competence of innovative and creative character; existence and work on methodological supplement), also psychological training and preparation for such activities (ability to create and stimulate positive educational atmosphere including age category of the students, readiness to solve pedagogical problems, work within the limits of using creative technologies of education and logical combination of traditional and innovational, creative methods of education etc.)
Keywords: психодидактичні проблеми; інноваційна діяльність педагога; сучасні креативні технології навчання